Dissipative Catalysis with a Molecular Machine. Issue 29 (21st June 2019) - Biagini, Chiara; Fielden, Stephen D. P.; Leigh, David A.; Schaufelberger, Fredrik; Di Stefano, Stefano; Thomas, Dean
Abstract: We report on catalysis by a fuel‐induced transient state of a synthetic molecular machine. A [2]rotaxane molecular shuttle containing secondary ammonium/amine and thiourea stations is converted between catalytically inactive and active states by pulses of a chemical fuel (trichloroacetic acid), which is itself decomposed by the machine and/or the presence of additional base. The ON‐state of the rotaxane catalyzes the reduction of a nitrostyrene by transfer hydrogenation. By varying the amount of fuel added, the lifetime of the rotaxane ON‐state can be regulated and temporal control of catalysis achieved. The system can be pulsed with chemical fuel several times in succession, with each pulse activating catalysis for a time period determined by the amount of fuel added. Dissipative catalysis by synthetic molecular machines has implications for the future design of networks that feature communication and signaling between the components. Abstract : An out‐of‐equilibrium state of a synthetic molecular machine is used to control catalysis. A rotaxane is transiently converted from a catalytically inactive state into an active form by CCl3 CO2 H. Deprotonation by the rotaxane promotes decarboxylation of the acid, thereby returning the system to its original state and stopping catalysis. This process allows temporal control of a coupled biomimetic reduction reaction.